2016
DOI: 10.1111/jcpe.12516
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy of single peri‐implantitis intrabony defects, by means of deproteinized bovine bone mineral with 10% collagen

Abstract: These results confirm the possibility to successfully treat peri-implantitis lesions. There is lack of evidence of whether or not the resolution of the peri-implant disease is associated with the defect configuration. Due to the fact that complete resolution does not seem a predictable outcome, the clinical decision on whether implants should be treated should be based on several patient related elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 35 publications
(77 reference statements)
4
92
0
Order By: Relevance
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients was 61 years (ranged from 20 to 83 years) with the mean observation period of 37 months (ranging from 12 to 236 months). Eleven studies [23-25,27,29,31,32,35-37,39] reported smoking status of the patients, ranging from 14% [39] to 72% [36]. The summarized individual study characteristics are described in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations